دور الشفافية في الحد من مظاهر الفساد الإداري دراســــة ميدانية في الشـــــركة العـــامة لمرفأ اللاذقية (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The purpose of the research is to identify the reality of the practice of transparency in its dimensions: accuracy and honesty in providing information, easy access to information, public information, in the General Company of Lattakia Port, and its role of reducing the manifestations of administrative corruption represented by: combating bribery and limiting the exploitation of the position. The study was based on the descriptive approach. The research society included all the administrative staff in the general company of Lattakia port. The sample of the research is a soft sample of (200) administrative workers, the questionnaires were distributed to them, 177 (complete questionnaire) (88.5%). The results showed that there is a strong and inverse relation between the commitment to transparency and the reduction of administrative corruption in the company under study. 77.9% of the variation in the reduction of administrative corruption is explained by the commitment to transparency. Contribute to the reduction of the manifestations of administrative corruption in the company under study, and this applies to every dimension of transparency (accuracy and honesty in providing information, accessibility of information, public information). هدف البحث إلى التعرف على واقع ممارسة الشفافية بأبعادها: الدقة والصدق في تقديم المعلومة, سهولة وصول المعلومة, علنية المعلومة, في الشركة العامة لمرفأ اللاذقية, ودورها من الحد من مظاهر الفساد الإداري المتمثلة بـ: مكافحة الرشوة, والحد من استغلال المنصب. اعتمد البحث المنهج الوصفي, وشمل مجتمع البحث جميع العاملين الإداريين في الشركة العامة لمرفأ اللاذقية, أما عينة البحث فهي عينة ميّسرة بلغ عدد أفرادها (200) عامل إداري تمّ توزيع الاستبانات عليهم, وأعيد منها (177) استبانة كاملة وصالحة للتحليل الإحصائي, وبنسبة استجابة بلغت (88.5%). أظهرت النتائج وجود علاقة عكسية وقوية ذات دلالة معنوية بين الالتزام بتطبيق الشفافية وبين الحد من مظاهر الفساد الإداري في الشركة محل الدراسة, حيث أنّ (77.9%) من التباين الحاصل في الحد من مظاهر الفساد الإداري يفسرها الالتزام بتطبيق الشفافية, وهذا يدل أنّ الالتزام بتطبيق الشفافية يسهم في الحد من مظاهر الفساد الإداري في الشركة محل الدراسة, وينطبق ذلك على كل بعد من أبعاد الشفافية المتمثلة في: الدقة والصدق في تقديم المعلومة, سهولة وصول المعلومة, علنية المعلومة.